Neuromagnetic responses reflect the temporal pitch change of regular interval sounds - Ritter, Steffen; Dosch, Hans Günter; Specht, Hans Joachim; Rupp, André (NeuroImage, 2005)
The pitch onset response (POR) evoked by the transition between two regular interval sounds (RIS) with different pitch was studied by recording the neuromagnetic responses with a 122-channel whole head magnetoencephalograph (MEG). The parameters of RIS were varied giving rise to characteristic changes in the latency of the first prominent deflection occurring about 100 to 140 ms after the transition. These latency differences of the neurophysiological signal correlated strongly with the psychoacoustic findings obtained from the same individuals. Some of the observed changes cannot be explained by obvious physical differences as changes in the spectrum, but only by temporal processing mechanisms as the auditory image model (Patterson, R.D., Allerhand, M., Giguere, C., 1995. Time-domain modelling of peripheral auditory processing: a modular architecture and a software platform. J. Acoust. Soc. Am. 98, 1890-1894). The location of the POR evoked by the transition was found to be in lateral Heschl's Gyrus, which gives further evidence that this is the center of processing pitch changes in the auditory cortex.